Globalizing intellectual property rights : the TRIPs agreement - Matthews, Duncan, 1965- (Routledge/Warwick studies in globalisation., 2002)
"In Globalising Intellectual Property Rights, Matthews looks at various aspects of the TRIPs Agreement - agenda-setting, legal interpretation, implementation, enforcement and revision - from the viewpoint of both global business interests and developing countries. It is argued that the Agreement was largely the result of an initiative by multinational companies who sought to protect their own intellectual property rights through international law and, furthermore, that it is these multinational companies who are now its main guardians. The book concludes that the history of the TRIPs Agreement and the role of business is a clear example of governance by non-state actors on a global scale." "This book will be of interest to students and researchers in the fields of international relations, intellectual property law, international economic law and development studies."--Jacket